PERTUMBUHAN TANAMAN NILAM (Pogostemon cablin Benth) PADA UJI KOMPOSISI MEDIA TANAM DAN SUMBER SETEK - Akbar, Ilham; Firmansyah, Amanda Patappari; Rosanna, Rosanna; Kasifah, Kasifah (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
The research aims to determine the growth rate of nilam plants based on the planting media's composition and the cuttings' source. This research was structured using a Randomized Block Design (RAK) with 2 factors, namely the first factor, namely the source of patchouli plant cuttings, namely stem cuttings (S1) and branch cuttings (S2), then the second factor, namely the planting media combination with a combination of M1 (2kg cow manure: 2kg husk: 1kg sand: 1kg soil), M2 (1kg cow manure: 1kg husk: 1kg sand: 1kg soil), M3 (2kg cow manure: 2kg husk: 2kg sand: 2kg soil). The parameters observed were the percentage of growth power (%), cutting height growth (cm), shoot height (cm), number of shoots, number of shaped leaves (strands), and root length (cm). The best growth rate for patchouli plant cuttings is stem cuttings (S1) with an average growth percentage (96.67%), increase in cutting height (11.66 cm), shoot height (2.82 cm), number of shoots ( 7), and the number of shaped leaves (17,13). The best type of planting media composition is the M1 treatment for observing the growth of cutting height, shoot height, number of shoots, number of leaves formed, and root length. The best interaction treatment is the source of stem cuttings with a combination of planting media (S1M1).